Lower-extremity bracing can improve postural stability during walking - Qu, Xingda (2013)
Falls are a major cause of injuries and fatalities. In order to avoid a fall, it is essential to maintain postural stability. The purpose of this study was to evaluate wearing lower-extremity supports as a fall prevention intervention to improve postural stability. Eleven older participants participated in this study. These participants were instructed to walk on a treadmill at their comfortable speeds under five testing conditions: no support, ankle support, calf support, knee support, and thigh support. Postural stability during walking was quantified by local dynamic stability measures derived from non-linear dynamics. The results showed that wearing the thigh support and ankle support can lead to improved local dynamic stability in the frontal plane and sagittal plane, respectively. Therefore, it might be concluded that wearing the thigh support and ankle support may be an effective fall prevention intervention for reducing fall risks. In addition, wearing lower-extremity support is also a practical fall prevention solution since lower-extremity supports are ease of use and cost effective.